Development energy monitoring system ising Internet of Things (IoT) - Ahad, Rosnee; Mustafa, Mohamad Zaid; Mohamad, Suhaimi; Abdullah, Nurhanim Saadah; Sumarwati, Sri (2021)
IoT is a term that symbolizes the relationship between objects or equipment using the internet. This study aims to develop an energy consumption monitoring system using the Internet of Things (IoT). The system development process in this study is an adaptation of the Waterfall model which contains five phases namely requirement, design, implementation, verification and maintenance phase. The findings of this study show that there are several problems that have been identified that are difficult to know the amount of energy used by a load, no facilities to monitor energy consumption remotely, data collected by kwj meters are not specific or detailed and methods of measuring electricity consumption are complicated and takes a long time. In conclusion, the energy consumption monitoring system using this IoT has successfully achieved the objectives set by the researchers. While the estimated cost for this system is also Rm200 which is an affordable price per user. With this system, researchers want to implement efficient energy usage while at the same time facilitating the use of consumers who want to do data analysis on energy usage. In addition, the researcher also hopes that future research can solve the problem and facilitate the user's business is doing something based on the suggestions and comments provided.